Digital Transformation in Government Administration: The Role of Technology-Based for Enhancing Public Satisfaction - R. Misriah Ariani S; Ria Adriyani; Ros Awaliyah Rosadah; Tri Amalia Sukarno; Fatin Hamamah (Journal of Business Management and Economic Development, 2026)
Digital transformation in government has become a key strategy in improving the effectiveness of public administration and the quality of services to the public. theory Modern and public administration the concept of e-government emphasizes the importance of digitalisation to achieve efficiency, transparency, and accountability in governance. However, the implementation of administrative digitalisation still faces various challenges, such as infrastructure readiness, digital literacy, and security data. The main problem faced is the extent to which technology-based administration is able to increase public satisfaction with government services. This study aims to analyse the role of digital transformation in increasing public public satisfaction with services, by identifying factors that support and hinder the effectiveness of its implementation. The research method used is a qualitative approach with case studies on several government agencies that have implemented digitalisation in public administration. Data were collected through interviews, observations, and analysis of official documents related to the implementation of e- government. The results showed that administrative digitalisation has a positive impact on improving accessibility, efficiency, and transparency of public services. However, its success is highly dependent on the readiness of technological infrastructure, supporting regulations, and public adaptation to digital services. The conclusion of this study confirms that technology-based administration plays a role important in improving public satisfaction, but comprehensive policies are needed to overcome the challenges of its implementation in order to realise more effective and inclusive public services. This study contributes to the field of public administration by offering an empirical model of digital transformation that synthesizes infrastructural readiness with user-centric satisfaction, serving as a critical reference for future research and inclusive e-government policy design.